معالم الفكر الإسلامي قبل ظهور الاتجاه السلفي بإندونيسيا (State Islamic University (UIN) of Sunan Ampel Surabaya, 2008)
It's difficult to speak of the characteristics of Islamic thought in Indonesia during the early period the 9th century until toward the end of the 16th century. The unavailability of the resources on this issue and the attitude of Indonesians in general that prefer spirituality rather than thought and ideas serve as the main reason for this difficulty. It is with this challenge in mind that is paper is designed. It is aimed at historically describing the development, characteristics and thrusts of Islamic thought in Indonesia prior to the advent of the salafi current of thought. It brings to light first, the irrevocable role of the Arabs, the Persians, and the Indians in the dissemination of Islam in the country. It argues that Islamic thought in Indonesia is influenced to a large extent by the dynamics of religious thought in these regions. Given its very nature, Islamic thought in Indonesia was impregnated by the dynamic tension between the Sunnites and the Shi‘ites, the Shafi‘ites and the non-Shafi‘ites, the Sunni Orthodox Tasawuf and the Philosophical Heterodox Tasawuf as well as between the Sunnites and the Batinites.